Analysis of the resistance to 7 antimicrobial agents in 100 strains of Neisseria gonorrhoeae - Xiao-dong LI; Jing-yao LIANG; Wen-ling CAO; Chao BI; Ping LI; Jian-qin WANG; Xi-bao ZHANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2020)
Objective: To analyse antimicrobial resistance of Neisseria gonorrhoeae to 7 antimicrobial agents and the penicillinase-producing Neisseria gonorrhoeae (PPNG) and tetracycline resistant Neisseria gonorrhoeae (TRNG) in Guangzhou during 2019. Methods: 100 Neisseria gonorrhoeae strains were isolated and cultured from our clinical department. Minimum inhibitory concentration (MIC) of penicillin, tetracycline, ciprofloxacin, spectinomycin, azithromycin, ceftriaxone, cefixime was determined by agar dilution method. β-lactamase was measured by paper iodine quantitative method. Results: PPNG and TRNG accounted for 35% (35/100) and 32% (32/100) of the Neisseria gonorrhoeae isolates, respectively.The antibiotic resistant rate of ciprofloxacin, penicillin and azithromycin was 99%(99/100)、93% (93/100) and 10% (10/100). Both moderate sensitivity rate of ceftriaxone and cefixime were 22% (22/100) and 19%(19/100), both sensitivity rate accounted for 78%(78/100) and 81%(81/100). All isolates were susceptible to spectinomycin. Conclusion: The resistant strains to spectinomycin, ceftriaxone and cefixime were not found and these antibiotics can still be used as the first drug for the treatment of Neisseria gonorrhoeae in Guangzhou. However, the dynamic changes in moderate sensitivity rate of ceftriaxone and cefixime show that it is essential to continuously monitor antimicrobial resistance of Neisseria gonorrhoeae for providing theoretical guidance to clinical rational antibacterial treatment.